Grasshoppers: row materials in traditional medicine (Mongolian Journal of Agricultural Sciences, 2015)
Preparations and medicaments derived from grasshoppers are mostly used for curing such diseases as respiratory disorders /65%/, wounds /16%/, poisoning /8%/, and trauma /11%/ in forms of simple extract /35%/, boiled extract /21%/,bolus /35%/ via swallowing /9%/, drinking /80%/, topical use /14%/ and fumigation /6%/. In total 8 species of grasshoppers of therapeutic values belonging to 4 genera have been identified.Caloric value of raw materials 1351,2 joule and contains up to 60 proteins, 16 amino acids, vitamins and various minerals. Toxicity of grasshoppers preparation is 8,1 ml/kg and the preparation has no adverse effects on animal body. The preparation exerts such effects as relieving the severity of edematous pneumonia, prolonging the life span, minimizing concentration of nitrogen oxide during inflammation as inhibitor, stopping oxidation and adaptability during oxygen deficiency and thermal exposures.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 75-79